The Last Mediterranean: Paul Theroux’s Obsessions Beyond the Pillars - El Annabi, Jawad (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
When Charlie Rose asked Paul Theroux about his reasons for writing about the Mediterranean, the subject of numerous other books in 1995, he said, “I don’t like other travel books, and this is my Mediterranean.” Theroux was a renowned travel writer and novelist known for his unconventional style and sharp satirical gaze. In 1993, he had set off on a journey of nine months through the Mediterranean and subsequently published The Pillars of Hercules: A Grand Tour of the Mediterranean (1995). The mid-1990s was an important period in American engagement with the world: the Cold War had ended, and the US, now the sole Superpower, had kicked its “Vietnam Syndrome” in the Persian Gulf War. While historians have begun to examine the renewed sense of American exceptionalism shaping political events of this era, my article contributes to understanding how cultural works reflected and also shaped this era by delving into this author’s narrative choices, his craft as a travel writer and ultimately his silences. Theroux was an idiosyncratic author who still spoke to a generation of readers. My study assesses Theroux’s narrative style as well as the people and places he chooses to visit and describe in his book. Theroux’s Mediterranean thus provides a gateway to understanding what this sea meant to him as an individual while also providing insight into a rapidly changing socio-cultural landscape in the US.